Pengaruh Kompensasi Terhadap Kinerja Karyawan Koperasi - Burhanudin; Iyan Tri Suryanto (Program Studi Magister Manajemen, Institut Manajemen Koperasi Indonesia, 2021)
The present study aimed to find out the effect of financial and non-financial compensation on employees’ performance. The participants of the study were sixty employees of Credit Union Dharma Kita Savings and Loans Cooperative, Sleman, Yogyakarta. The data were collected using questionnaire. Multiple linear regression was applied to analyze the data. The result of the study showed that financial compensation did not affect the Credit Union Dharma Kita Savings and Loans Cooperative employees’ performance, whereas non-financial compensation was reported to affect the Credit Union Dharma Kita Savings and Loans Cooperative employees’ performance.